Effect of post-fire ecological restoration on the arboreal diversity of the Chipinque Ecological Park, Mexico - Alanís-Rodríguez, Eduardo; Jiménez-Pérez, Javier; Pando-Moreno, Marisela; Aguirre-Calderón, Óscar A.; Treviño-Garza, Eduardo J.; García-Galindo, Perla C. (Instituto de Ecología, A.C., 2016)
The temperate forests of Chipinque Ecological Park (PECh) are of great importance due to environmental services they provided to the Metropolitan Area of Monterrey. In 1998 was raised a forest fire that affected the third part of the PECh. In the area post-fire was performed an ecological restoration program. In 2008 (ten years after) was conducted a comparative analysis of the diversity of the arboreal component of the restored area and naturally regenerated. The objective was to determine whether there are statistical differences in tree diversity (number and species density, and vertical and horizontal structure) between the two areas. By means of species-area curve was determinated the establishment of four sampling units of 100 m2 in each area. Were 8 families, 10 genera and 14 species. The genus with more presence in both areas was Quercus. The second specie more important in restored area was Pinus pseudostrobus. According to vertical analysis of arboreal layer was concluded that both areas are multicohorts. Referring to ß diversity the evaluated areas presented a mediumhigh similarity. The restored area and regenerated not present statistical differences in the diversity-abundance (t= 0 ,55, g.l.=1269,63, p<0,05), abundance (t=0,16) and dominance (t=0,26). This research generated quantitative information that indicates that the silvicultural practices employed for ecological restoration increased the density of P. pseudostrobus, without altering the diversity, abundance and dominance of the trees.